Probing magnetic order and disorder in the one-dimensional molecular spin chains CuF2(pyz) and [Ln(hfac)3(boaDTDA)] n (Ln = Sm, La) using implanted muons - Lancaster, T; Huddart, BM; Williams, RC; Xiao, F; Franke, KJA; Baker, PJ; Pratt, FL; Blundell, SJ; Schlueter, JA; Mills, MB; Maahs, AC; Preuss, KE (IOP Publishing, 2019)
We present the results of muon-spin relaxation ([Formula: see text]SR) measurements on antiferromagnetic and ferromagnetic spin chains. In antiferromagnetic CuF2(pyz) we identify a transition to long range magnetic order taking place at [Formula: see text] K, allowing us to estimate a ratio with the intrachain exchange of [Formula: see text] and the ratio of interchain to intrachain exchange coupling as [Formula: see text]. The ferromagnetic chain [Sm(hfac)3(boaDTDA)] n undergoes an ordering transition at [Formula: see text] K, seen via a broad freezing of dynamic fluctuations on the muon (microsecond) timescale and implying [Formula: see text]. The ordered radical moment continues to fluctuate on this timescale down to 0.3 K, while the Sm moments remain disordered. In contrast, the radical spins in [La(hfac)3(boaDTDA)] n remain magnetically disordered down to T  =  0.1 K suggesting [Formula: see text].